Pengembangan dan Pelestarian Terhadap Destinasi Objek Wisata Desa Bungabali Kecamatan Pantar Timur menjadi Sektor Andalan Masa Sekarang dan Masa yang Akan Datang - Melki Imamastri Puling Tang; Abraham Boling Wabang; Werner M. Adisaputra; Triloisza Mau (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2023)
Bungabali Village is a village in the coastal area located in East Pantar District, Alor Regency. This village has great potential to be developed into a tourist village in the future, so mapping the existing potential is needed. If you see the existence of potential that exists when developed when promising.This research will be carried out with qualitative methods as a research approach, with the purpose of research with a qualitative approach is to examine, explain, describe, describe critically, or describe a social phenomenon that occurs in society and researchers play a role in finding the meaning of the phenomenon.The results showed that the existence of the Sakrawang sacred grave site commonly called Bom Sakraung ge bere, the natural beauty of the underwater around Tanjung Kelelaka or other names Alalari - Abangiwang, the unique village of Weniwa-Matgom Abang and around the nature of Abangiwang Bungabali village.The cool and beautiful village is a tourist destination that should be maintained, developed and preserved optimally. Lego culture commonly known as Lego-lego Sukhai and Daro is a cultural art that should be maintained from generation to generation. The sacred grave site of Bom Sakraung. The surrounding community has traditionally considered him a hero who is able to kill an eight-pronged snake or a snake with an eight-pronged head or the name of the surrounding community calls Dam Gong Yentug or Dam Gong Takhamung Yentukhamung Yentug in the Gong Takhamung Buk'u area, precisely located in the Kaera Padangsul village area, East Pantar District.